Cell type-selective imaging and profiling of newly synthesized proteomes by using puromycin analogues. Issue 60 (12th July 2017) - Du, Shubo; Wang, Danyang; Lee, Jun-Seok; Peng, Bo; Ge, Jingyan; Yao, Shao Q.
Abstract : We have developed a versatile antibody-assisted strategy for the imaging and profiling of newly synthesized proteomes in a cell-specific manner. Abstract : We have developed a versatile antibody-assisted strategy for the imaging and profiling of newly synthesized proteomes in a cell-specific manner. This strategy remained highly selective even in heterogeneous co-cultured cells, thus enabling labeling and enrichment of nascent proteomes from targeted cells without the need for physical separation.